Implementasi Evaluasi Pembelajaran Tematik di Sekolah Dasar Negeri Cipondoh 3 Tangerang - Ina Magdalena; Diah Vitaloka; Elismawati Elismawati; Khaerina Sasmita Aji (RC-INSTITUT, 2020)
The implementation of thematic learning evaluation in elementary schools is an important thing to do so that the expected goals are achieved, especially in the curriculum itself, one form of education implementation is thematic learning that promotes knowledge comprehensively and integrity. The research method used is descriptive qualitative, describing the results of the study. The data collection technique used by researchers interviewed The research was conducted at SDN Cipondoh 3 Tangerang. Evaluations are carried out in the form of processes and results. This thematic learning evaluation implementation has been going very well, supported by the fulfillment of National Education standards and teachers who have good motivation, creativity, and performance.